الشعر العربي النيجيري ومقاومة الأخلاق الرذيلة - A. Asalejo, Abdulrafu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
This paper sheds light on the Nigerian Arabic literary poetry that preaches against immorality. It is an analytical study of some sample poems of some Nigerian-Arabic literati in whose preaching against social vices such as adultery, immodesty, abasement and alcoholism is echoed. The paper examines linguistic and literary meaning of immorality, and how the Nigerian-Arabic literary scholars have expressed the religious prohibitions of these social vices in their works. The work equally literally analyzes these poetry and concludes that the activities of the Nigerian-Arabic literati showcase their Islamic proselytization through their literary works